2023
DOI: 10.17485/ijst/v16i8.27
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Curie Point Depth Using High Resolution Aeromagnetic of Igumale and Ejekwe Area, Lower Benue Trough Nigeria

Abstract: Objective: To carryout geophysical investigation in Igumale and Ejekwe area with the aim of estimating the Curie point depth (CPD) and then evaluating the geothermal gradient and heat flow to see if it is viable for geothermal exploration. Methods: Spectral analysis method was employed in this research work. Findings: The results show that the CPD varies between 1.111 and 17.402km. It is observed that the CPD in the Eastern part of the study area (11 -12.6km) is shallower when compared to the other parts of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Therefore, it is imperative to step up efforts to explore geothermal energy-rich locations in Nigeria. https://www.indjst.org/ Some researchers have deployed aeromagnetic method in search for potential area of geothermal energy at different Basins in Nigeria (1)(2)(3)(4)(5)(6)(7)(8) . Few recent geothermal research has been reported in Upper Benue Trough (9,10) but not in all parts of the Upper Benue Trough.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is imperative to step up efforts to explore geothermal energy-rich locations in Nigeria. https://www.indjst.org/ Some researchers have deployed aeromagnetic method in search for potential area of geothermal energy at different Basins in Nigeria (1)(2)(3)(4)(5)(6)(7)(8) . Few recent geothermal research has been reported in Upper Benue Trough (9,10) but not in all parts of the Upper Benue Trough.…”
Section: Introductionmentioning
confidence: 99%